Isolation of Peanut Stripe Virus from Infected Leaves : a Comparison between Supporting Plants and Insects - Thongpan, Amara; Boonkemthong, Chainarong (Agriculture and Natural Resources, 1998)
Two isolated methods of peanut stripe virus (PStV) from naturally virus-infected peanut leaves (Chenopodium quinoa) were compared. Transmiting the virus to Chenopodium amaranticolor leaves using leaf-rubbing technique and then isolation appeared to be more reliable and less time-consuming than using insect (Aphis craccivora Koch.) as virus carrier. Although the insect was very effective in carrying the PStV to uninfected peanut leaves, it was not PStV-specific transmission. Moreover, it took longer time to cause any visible damage on peanut leaves than on C. amaranticolor leaves caused by leaf-rubbing. The study also demonstrated that peanut Phaseolus vulgaris cv. Master Piece could be one of the supporting plants for PStV; however, the symptom appeared to be different from those found on C. amaranticolor or C. quinoa leaves.